Innovation subsidies: Does the funding source matter for innovation intensity and performance? Empirical evidence from Germany - Dirk Czarnitzki; Cindy Lopes Bento (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
Applying a variant of a non-parametric matching estimator, we consider European funding and national funding as heterogeneous treatments, distinguishing and simultaneously analyzing the effect these treatments have on innovation input and performance. In terms of input, getting funding from both sources yields the highest impact. If funding from only one source is received, EU grants have higher effects. In terms of output, holding innovation expenditures constant, funding from both sources display higher sales of market novelties and future patent applications at the firm level. If only one grant is obtained, we find superiority for national funding.
Keywords: C14; H50; O38; 330; Subsidies; Innovation; Policy Evaluation; Treatment Effects; Nonparametric matching estimation; Innovationspolitik; Subvention; Wirkungsanalyse; Innovation; Unternehmensentwicklung; Schätzung; EU-Staaten